1983
DOI: 10.1007/bf00918010
|View full text |Cite
|
Sign up to set email alerts
|

Physiological regulation of vascular permeability by endogenous glucocorticoids and active oxygen

Abstract: A copper chelator, diethyldithiocarbamate (DDC), injection and adrenalectomy induce significant paw swelling by low doses of serotonin, histamine, or bradykinin, which can result in mild swelling in non-treated mice. Dexamethasone, Cu,Zn-superoxide dismutase (SOD), and hydroxyl radical scavengers suppressed the DDC-provoked edema, but only dexamethasone suppressed the edema of adrenalectomized mice. Adrenal stimulation by SOD is exclusive in that the suppression of edema by SOD began about 1 h prior to that by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Vasoregulin easily lost its anti-inflammatory potency on incubation with a superoxide radical generating system in vitro. Together with results of our previous reports [5,8], we present the site of action of vasoregulin in Fig. 7.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Vasoregulin easily lost its anti-inflammatory potency on incubation with a superoxide radical generating system in vitro. Together with results of our previous reports [5,8], we present the site of action of vasoregulin in Fig. 7.…”
Section: Discussionsupporting
confidence: 70%
“…[13] and pointed out by us [8]. Free arachidonic acid results in the sudden death of rabbits by pulmonary thrombosis which can be efficiently prevented by dexamethasone treatment [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the present study showed that a deficiency of glucocorticoids by itself induced a significant increase in gastric microvascular permeability in adrenalectomized rats and that this increase was totally prevented by corticosterone replacement. Glucocorticoids are known to decrease vascular permeability by inducing production of the anti-inflammatory protein vasoregulin (26,27). Because vascular permeability is enhanced by vascular endothelial growth factor (VEGF) (3), and because the expression of VEGF is stimulated by hypoglycemia (31) and inhibited by glucocorticoids (23), it is possible that the effect of corticosterone on gastric microvascular permeability is mediated by downregulation of VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Mediator-induced plasma extravasation is known to occur in postcapillary venules (7,8) and is believed to be due to conformational changes ofendothelial cells (28). It has been suggested that glucocorticoids inhibit mediator-induced extravasation through the synthesis of inhibitory proteins that oppose the conformational changes of endothelial cells (29)(30)(31)). Our present observation that the same dose of dexamethasone that markedly inhibits substance P-induced extravasation has no effect on PAF-induced extravasation is inconsistent with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%